Religious Nationalism in a Global World - Juergensmeyer, Mark (Religions, 2019)
The rise of new forms of religious nationalism at the end of the 20th and beginning of the 21st centuries is to a large extent a by-product of globalization. As nation-states are permeated by transnational economics and trends and secular nationalism is challenged by the global diaspora of peoples and cultures, new ethno-religious movements have arisen to shore up a sense of national community and purpose. One can project at least three different futures for religious and ethnic nationalism in a global world: one where religious and ethnic politics ignore globalization, where they rail against it, and where they envision their own transnational futures.